New Insights Into Novel Therapeutic Targets in ANCA-Associated Vasculitis - Nozaki, Yuji (Frontiers in Immunology, 2021)
Biologics targeting inflammation-related molecules in the immune system have been developed to treat the rheumatoid arthritis. The therapeutic system has made revolutionary advances. With the accumulation of clinical experience and advances in understanding the pathogenesis of vasculitis, it is becoming increasingly difficult to cure. Biologics have been attempted for the treatment of vasculitis in the clinical trials. Particularly in patients with resistance to standard treatments, it could be an effective treatment for ANCA-associated vasculitis. It has also been effective in enhancing our understanding of the pathogenesis of vasculitis. Recently, mepolizumab, which is a humanised anti-interleukin 5 monoclonal antibody, shows clinical benefit in the management of eosinophilic granulomatosis with polyangiitis in the refractory and relapsing disease. Thus, some of these new drugs are in clinical trials in vasculitis, while others are in abeyance. This review highlights the new findings of biologics in the addition to the conventional immunosuppressive therapy in ANCA-associated vasculitis.